The Impact of the Quality of the Work Environment on the Success of Al-Rashid Trading and Contracting Company Projects in Riyadh City (International Journal of Financial, Administrative and Economic Sciences, 2024)
Since quality is one of the most important things in life, and it is one of the goals of Vision 2030 for the Kingdom of Saudi Arabia, therefore Al-Rashed Trading and Contracting Company in the city of Riyadh seeks to achieve sustainable success in its projects, by focusing on the factors that greatly influence the achievement of this goal, and among the most important The factors are the quality of the work environment within the organization. There are also several other factors that reflect on the quality of the work environment, such as effective communication, trust between teams, high morale, and interest in the personal and professional development of employees. The aim of this study was: to determine the impact of the quality of the work environment on the success of the projects of Al-Rashed Trading and Contracting Company, to discover the factors affecting the quality of the work environment and its impact on the performance of projects, to provide recommendations to improve the quality of the work environment in the company, and to enhance the success of the projects. This study relied on a descriptive and analytical research approach, as well as a field research approach, using the Google Forms statistical tool by distributing an electronic questionnaire to male and female employees. The questionnaire was distributed to (350) individuals, and (303) responses were received, as a group refused. From conducting the questionnaire, a survey sample of (31) individuals from Al-Rashed Trading and Contracting Company employees was distributed from outside the actual sample of the study (comprehensive survey), equivalent to 10% of the total sample, to verify the validity of the internal consistency of the questionnaire.The study concluded that the quality of the work environment is affected by the company's policies and organizational culture, and therefore managing these elements effectively can enhance the success of the company's projects. A healthy and encouraging work environment must also be provided, as this leads to increased employee satisfaction and productivity, which reflects positively on the quality of services and products provided by the company, and thus is reflected in the success of its projects. Accordingly, Al-Rashed Trading and Contracting Company should pay attention to improving the quality of the work environment, and ensuring that it is conducive to the well-being and productivity of its employees, and this in turn will contribute to achieving the sustainable success of its projects in the city of Riyadh.
Keywords: Al-Rashed Trading and Contracting Company; Quality of Work Environment; Production; Employees; Creativity and Innovation; Project Success